2010
DOI: 10.1089/jwh.2008.1210
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Factors, Hormonal Contraception, and Premenstrual Symptoms: The United Kingdom Southampton Women's Survey

Abstract: Premenstrual symptoms were common in this cohort. Use of hormonal contraceptive methods was associated with a lower prevalence of these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
62
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 29 publications
14
62
0
4
Order By: Relevance
“…The prevalence was higher than study done in United Kingdom Southampton Of the women surveyed, 24% were considered to have premenstrual symptoms (95% confidence interval, the possible reason might be the difference of instruments used to assess premenstrual syndrome ,this might also be due to the different study design and sample size North Showa, Amhara Region, Ethiopia used (14).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The prevalence was higher than study done in United Kingdom Southampton Of the women surveyed, 24% were considered to have premenstrual symptoms (95% confidence interval, the possible reason might be the difference of instruments used to assess premenstrual syndrome ,this might also be due to the different study design and sample size North Showa, Amhara Region, Ethiopia used (14).…”
Section: Discussionmentioning
confidence: 66%
“…Women were less likely to have symptoms if they had higher levels of educational attainment and suffered less from stress. No associations were found between premenstrual symptoms and diet, alcohol, or strenuous exercise or after adjustment for other factors, with age, smoking, or body mass index (BMI) (14).…”
Section: Introductionmentioning
confidence: 98%
“…Mixed results were produced from 13 studies investigating the association between age and PMS/PMDD. Four studies [22,115,122,142] suggested that younger age was related to a higher risk of PMS with an odds ratio of up to two, whilst eight studies failed to detect a significant association [25,110,113,118,120,123,125,126]. The other two multi-country studies among women from Europe and Latin America [111] and Asia [141], revealed a inverse U-shaped effect of age on the intensity of PMS (using a total duration and severity index), with the peak prevalence around age 35 years.…”
Section: Demographicsmentioning
confidence: 98%
“…Five longitudinal [22,25,26,108,109] and 17 community-based cross-sectional studies [110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] reported on the prevalence and/or incidence rates of PMS/PMDD. The results from the studies are summarised in Table 3-9.…”
Section: Prevalence and Incidence Of Pms/pmddmentioning
confidence: 99%
See 1 more Smart Citation